Women's Language Features in “Emma Chamberlain's" Vlogs - I Gusti Ayu Vina Widiadnya Putri; Putu Nur Ayomi; Ni Kadek Intan Permata Sari Dewi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
ABSTRACT This study aims to analysed the women's language features and the functions of women's language features found in the Vlog by Emma Chamberlain. The data were taken from the Vlog by Emma Chamberlain on YouTube. This study was analysed by applying the theory by Lakoff (1975) and the theory by Pearson (1985). Based on the phenomenon, women tend to talk in the media or digital communication. The trend of digital communication is called Vlog or video blogging. In total there are 8 data found in the Vlog from 6 videos. It can be concluded that, there were only Lexical Hedges, intensifiers, and hypercorrect grammars, tag question, rising intonation and declaratives, super polite form, Avoidance of strong swear, and emphatic stress were found in Emma Chamberlain’s Vlog. The functions, it was only found 3 functions from 5 function of women language features proposed by Pearson (1985). These functions are to start discussion, to get response, and to express feeling. The result, It can be concluded that to express feeling is the most commonly found. While, to get responds and to start discussion are the least found.